2015
DOI: 10.1210/en.2014-1717
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Dulaglutide on Thyroid C Cells and Serum Calcitonin in Male Monkeys

Abstract: Glucagon-like peptide-1 (GLP-1) receptor agonists, used for the treatment of type 2 diabetes, have caused hyperplasia/neoplasia of thyroid C cells in rodent carcinogenicity studies. Studies in monkeys have not identified an effect of GLP-1 receptor agonists on thyroid C cells; however, group sizes were small. Dulaglutide is a once-weekly, long-acting human GLP-1 receptor agonist recently approved in the United States and the European Union. The objective of this study was to determine whether dulaglutide alter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
7
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 26 publications
3
7
0
Order By: Relevance
“…Dulaglutide was assessed in nonhuman primates in a companion study (17) to the 52-week rat study reported here and no effects on thyroid C cells were detected based on quantitative assessment of C-cell mass, provocative testing for serum calcitonin, and systematic histological examination. Likewise, studies in dogs with lixisenatide have not shown effects on thyroid C cells.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Dulaglutide was assessed in nonhuman primates in a companion study (17) to the 52-week rat study reported here and no effects on thyroid C cells were detected based on quantitative assessment of C-cell mass, provocative testing for serum calcitonin, and systematic histological examination. Likewise, studies in dogs with lixisenatide have not shown effects on thyroid C cells.…”
Section: Discussionmentioning
confidence: 95%
“…The end points evaluated included basal and CaCl 2 -stimulated plasma calcitonin concentrations, thyroid weight parameters, histopathology, and morphometric evaluations of the thyroid. This 52-week rat study was conducted in parallel with another 52-week study in nonhuman primates that included extensive evaluation of thyroid C cells (17).…”
mentioning
confidence: 99%
“…In contrast to the results in rodents, in vivo animal studies with cynomologus monkeys did not show any liraglutideinduced calcitonin release or any effect on relative C-cell fraction in the thyroid gland after 87 weeks at doses up to 60-fold higher than the highest dose recommended in humans [169]. Another study in monkeys also showed that dulaglutide at doses amounting to the 500-fold maximum human plasma exposure for 52 weeks were not associated with increases in serum calcitonin or alterations in thyroid weight, histology, C-cell proliferation, or absolute/relative C-cell volume [171].…”
Section: Cancermentioning
confidence: 97%
“…Regulatory concerns surrounding the risk of thyroid C-cell hyperplasia and medullary thyroid carcinoma (MTC) were based entirely on data from mice and rats, which express the canonical GLP-1R on thyroid C cells, linked to stimulation of calcitonin secretion and C-cell proliferation (66,67). In contrast, it is difficult to detect GLP-1R expression within primate thyroid C cells (67), and sustained GLP-1R agonism does not induce C-cell hyperplasia in monkeys (67,68). Indeed, associated reports of GLP-1R expression within the normal and neoplastic human thyroid (69) reflected the use of nonspecific, incompletely validated GLP-1R antisera not suitable for detection of the GLP-1R (32,51).…”
Section: Adverse Events Associated With Glp-1r Agonistsmentioning
confidence: 99%